Transformation of chicken embryo fibroblasts and tumor induction by the middle T antigen of polyomavirus carried in an avian retroviral vector. - Kornbluth, S (1986)
The middle T antigen of polyomavirus transformed primary chicken embryo fibroblasts when expressed from a replication-competent avian retrovirus. This in vitro-constructed retrovirus, SRMT1, is a variant of Rous sarcoma virus that encodes the middle T antigen in place of v-src. Inoculation of SRMT1 into 1-week-old chickens rapidly induced hemangiomas and hemangiosarcomas. As shown with mammalian cells infected with polyomavirus, polyomavirus middle T antigen appears to be associated with p60c-src in chicken cells infected with SRMT1. When lysates of SRMT1-infected cells immunoprecipitated with either a monoclonal antibody against p60src or anti-T serum were assayed in an in vitro kinase reaction, the middle T antigen was heavily phosphorylated. To see whether an excess of p60c-src could alter the extent of phosphorylation of the middle T protein or the process of cell transformation by middle T, cells were doubly infected with SRMT1 and NY501, a virus which overexpresses p60c-src. Doubly infected chicken embryo fibroblasts transformed with the same kinetics and were morphologically indistinguishable from chicken embryo fibroblasts infected with SRMT1 alone. Phosphorylation of the middle T antigen was elevated two- to fivefold relative to cells infected only with SRMT1.